Pressure Drop and Void Fraction of Two-Phase Flow (Air-Water) in Grooved Vertical Pipes - Supa Kusuma Aji; Nicky Suwandhy; Chandra Gunawan; Bayu Pranoto; Hangga Wicaksono (Mekanika)
In an industrial environment, Two-phase flows has many weaknesses, including pressure drop and void fraction. One strategy to reduce losses that arise is to use passive methods. The passive method used is to utilize the shape of the grooves in the channel. In this study, the flow is used to determine its effect on the pressure drop and void fraction that appears in two-phase flow. The experimental method was used for this study. The test pipe is equipped with 16 grooves, while the smooth pipe (without grooves) is used as a comparison. The test pipe is made of acrylic material. The water fluid is circulated using a centrifugal water pump with a superficial speed of 0.33-0.42 m/s. Air fluid is supplied using a compressor with superficial speeds of 0.049, 0.066, and 0.082 m/s. Measurement of pressure drop was carried out using a pressure transmitter with an Arduino data logger. The void fraction is calculated by determining the ratio of the volume fraction of water and air in the test tube. The results of the study revealed that the use of 16 grooves in the pipe can reduce the pressure drop and cavity fraction that appears when compared to smooth pipes.